2014
DOI: 10.1007/s10577-014-9401-4
|View full text |Cite|
|
Sign up to set email alerts
|

Tribe-specific satellite DNA in non-domestic Bovidae

Abstract: Satellite sequences present in the centromeric and pericentric regions of chromosomes represent useful source of information. Changes in satellite DNA composition may coincide with the speciation and serve as valuable markers of phylogenetic relationships. Here, we examined satellite DNA clones isolated by laser microdissection of centromeric regions of 38 bovid species and categorized them into three types. Sat I sequences from members of Bovini/Tragelaphini/Boselaphini are similar to the well-documented 1.71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 49 publications
1
43
0
1
Order By: Relevance
“…However, the copy number of centromeric repeats on the bi-armed VVU chromosomes is not sufficient for the production of a detectable signal with the canine satellite DNA probe. The reduction of centromeric heterochromatin on biarmed chromosomes, compared to acrocentrics, was previously reported, e.g., among Artiodactyla and Rodentia [Modi et al, 1996;Kopecna et al, 2014;Louzada et al, 2015]. (2) Assuming a low chromosome number in the ancestral carnivore karyotype (2n = 38), the domestic dog (2n = 78) seems to represent one of the most derived karyotypes among Canidae [Graphodatsky et al, 2001;Nash et al, 2008].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, the copy number of centromeric repeats on the bi-armed VVU chromosomes is not sufficient for the production of a detectable signal with the canine satellite DNA probe. The reduction of centromeric heterochromatin on biarmed chromosomes, compared to acrocentrics, was previously reported, e.g., among Artiodactyla and Rodentia [Modi et al, 1996;Kopecna et al, 2014;Louzada et al, 2015]. (2) Assuming a low chromosome number in the ancestral carnivore karyotype (2n = 38), the domestic dog (2n = 78) seems to represent one of the most derived karyotypes among Canidae [Graphodatsky et al, 2001;Nash et al, 2008].…”
Section: Discussionmentioning
confidence: 71%
“…Among them, satellite DNAs, usually present as multiple tandem repeats spanning up to several megabases, are dominant components of the centromeric and pericentromeric heterochromatin [Charlesworth et al, 1994;Shiels et al, 1997]. The abundance, nucleotide sequence, and chromosomal location of satellite DNAs can vary among phylogenetically related species, and their comparative analysis can serve as a tool for mapping evolutionary processes and speciation [Bachmann and Sperlich, 1993;Slamovits et al, 2001;Plohl et al, 2008;Kopecna et al, 2014].The family Canidae is a complex taxonomic group consisting of 36 species which diverged from the common ancestor 10 Mya [Vilà et al, 1999; Graphodatsky et Keywords B chromosomes · Canidae · Centromere · Dog · Fluorescence in situ hybridisation · Red fox · Satellite DNA Abstract Satellite DNA is a characteristic component of mammalian centromeric heterochromatin, and a comparative analysis of its evolutionary dynamics can be used for phylogenetic studies. We analysed satellite and satellite-like DNA sequences available in NCBI for 4 species of the family Canidae (red fox, Vulpes vulpes , VVU; domestic dog, Canis familiaris , CFA; arctic fox, Vulpes lagopus , VLA; raccoon dog, Nyctereutes procyonoides procyonoides , NPR) by comparative sequence analysis, which revealed 86-90% intraspecies and 76-79% interspecies similarity.…”
mentioning
confidence: 99%
“…Several studies reported the presence of bovine SATI within several species of the Bovidae family and even in other families of pecoran ruminants (Modi et al 1996;Chaves et al 2000aChaves et al , 2005Kopecna et al 2012Kopecna et al , 2014 showing some ambiguities in some tribes. In 1996, Modi et al did not detect hybridisation signals in Hippotragini, Antilopini and Tragelaphini tribes, in contrast with the results reported by more recent studies (Chaves et al 2005;Kopecna et al 2012Kopecna et al , 2014. The SATI clone used by Chaves et al (2005) and the one used by Kopecna et al (2012) showed 96% similarity; however, some results of the two studies also diverged, concerning the Figure 3.…”
Section: Physical Distribution Of Bovine Satdnas Across Bovidaementioning
confidence: 99%
“…The first studies on mammalian satellite DNA (satDNAtandemly repeated DNA sequences) date back to the 1960s and 1970s and were carried out in the mouse, guinea pig and bovine genomes (Pardue & Gall 1970;Hsu & Benirschke 1973;Macaya et al 1978). SatDNA families have now been reported in numerous species, giving evidence of the sequences' evolutionary mechanisms, disclosing phylogenetic relationships between related species, showing details of autosomal and sex chromosome evolution or rearrangement, and helping scientists to understand functions of these ubiquitous DNA sequences (Chaves et al 2004;Adega et al 2009;Giannuzzi et al 2012;Kopecna et al 2012Kopecna et al , 2014Rojo et al 2015). Satellite DNA has potential structural and functional roles relating to centromeric function, chromosome stability, and meiotic pairing or segregation (Schmidt & Heslop-Harrison 1998;Plohl et al 2008;Adega et al 2009;Giannuzzi et al 2012;Ferreira et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation